SIMRS Success through User Satisfaction Using DeLone McLean and Demographic Factors - Tria Saras Pertiwi; Natalia Vanesia Setiawan; Hosizah Markam; Imam Sutanto (Universitas Duta Bangsa Surakarta, 2026)
Digital transformation in the healthcare sector encourages hospitals to adopt Hospital Information Systems (HIS), known in Indonesia as SIMRS to improve service efficiency and data management quality. However, the success of SIMRS implementation is strongly influenced by system quality, information quality, service quality, and users’ perceptions of the technology. This study aims to evaluate the success factors of SIMRS at RSIJ Pondok Kopi by integrating Perceived Usefulness and demographic factors into the DeLone and McLean (D&M) Information System Success Model through user satisfaction. This research methode is a quantitative design with cross sectional study using the PLS-SEM approach. The sample consisted of 62 SIMRS users selected using a total sampling technique. The study was conducted from May to August 2025. The results show that information quality and system quality significantly affect perceived usefulness, perceived usefulness significantly affects user satisfaction, and user satisfaction significantly affects net benefits. In addition, perceived usefulness has a significant indirect effect on net benefits. Meanwhile, demographic factors are not the main determinants of SIMRS success. Therefore, hospital management is recommended to prioritize improving information quality to optimize the effectiveness of SIMRS implementation.